Internalisasi Nilai-Nilai Ahlussunnah wal Jama’ah melalui Sekolah Aswaja di Perguruan Tinggi - Anwar, Ali (Lembaga Pendidikan Tinggi Nahdlatul Ulama (LPT NU) PCNU Kabupaten Nganjuk, 2026)
This study aims to analyze the internalization of Ahlussunnah wal Jama’ah values through Aswaja School programs in higher education. The values examined include tasamuh (tolerance), tawasuth (moderation), tawazun (balance), and ta‘adul (justice), which constitute the core principles of Aswaja teachings in shaping students’ character. This research employs a qualitative approach with a descriptive design. Data were collected through observation, in-depth interviews, and documentation related to the implementation of Aswaja School activities. Data analysis was conducted through data reduction, data display, and conclusion drawing in a systematic manner. The findings reveal that the internalization of Ahlussunnah wal Jama’ah values is carried out through integrated intracurricular, co-curricular, and extracurricular activities within the academic environment. These activities contribute to the development of students’ tolerant, moderate, balanced, and fair attitudes, while fostering openness to new knowledge without abandoning Islamic values. Furthermore, continuous innovation in the management of Aswaja School programs strengthens students’ understanding and practical application of Aswaja values in their social and academic lives. This study highlights the strategic role of Aswaja-based education in promoting value-based character formation in higher education.